Long-term safety and efficacy of dupilumab in patients with moderate-to-severe asthma (TRAVERSE): an open-label extension study. Issue 1 (January 2022) - Wechsler, Michael E; Ford, Linda B; Maspero, Jorge F; Pavord, Ian D; Papi, Alberto; Bourdin, Arnaud; Watz, Henrik; Castro, Mario; Nenasheva, Natalia M; Tohda, Yuji; Langton, David; Cardona, Guido; et al.
Summary: Background: Clinical trials have shown treatment benefits of dupilumab in patients with uncontrolled asthma for up to 1 year. This study aimed to evaluate the long-term safety and efficacy of dupilumab in patients with moderate-to-severe asthma, as data for extended treatment with dupilumab beyond 1 year are not available. Methods: TRAVERSE was an open-label extension study in 362 hospitals and clinical centres across 27 countries that assessed the safety and efficacy of dupilumab 300 mg every 2 weeks up to 96 weeks in adults and adolescents (aged 12–84 years) with moderate-to-severe or oral-corticosteroid-dependent severe asthma who had completed a previous dupilumab asthma study (phase 2A EXPEDITION, phase 2B DRI [P2b], phase 3 QUEST, or VENTURE). The primary endpoint was the number and percentage of patients with any treatment-emergent adverse events. Secondary endpoints included annualised exacerbation rate (AER) over the treatment period and change from parent study baseline in pre-bronchodilator FEV1, the five-item asthma control questionnaire (ACQ-5), the asthma quality of life questionnaire (AQLQ), type 2 biomarkers (blood eosinophils and serum total IgE), and anti-drug antibodies (ADAs). Statistical analyses were descriptive. We report safety in all enrolled patients, and efficacy in patients with non-oral-corticosteroid-dependent asthma and in subgroups, including patients with a type 2 inflammatory phenotype who received 148 weeks of treatment. This study is registered with ClinicalTrials.gov, NCT02134028 . Findings: Between Aug 5, 2014, and Oct 11, 2019, of 2302 patients assessed for eligibility, 2282 adults and adolescents were enrolled (median age 50 years, 62·1% female and 37·9% male). Safety during TRAVERSE was consistent with the known dupilumab safety profile. The proportion of patients reporting treatment-emergent adverse events throughout the study duration was similar to that observed in the parent studies and ranged from 76·3% to 94·7%. The most frequently reported treatment-emergent adverse events were nasopharyngitis (17·5–25·9%), injection-site erythema (2·2–23·4%), and bronchitis (9·3–19·0%). Serious asthma exacerbations (0·5–3·6%) and pneumonia (0·7–2·7%) were the most frequently reported serious adverse events. There were four treatment-emergent adverse events leading to death. Efficacy during TRAVERSE was also consistent with the results of parent studies. In patients who were non-oral-corticosteroid-dependent, AER remained low (0·277–0·327) across parent study and treatment groups, pre-bronchodilator FEV1 improvements were sustained to the end of treatment at week 96 (mean changes from parent study baseline ranged from 0·22 L [SD 0·44] to 0·33 L [0·44] across parent study and treatment groups), and improvements in ACQ-5 and AQLQ scores were sustained to the last timepoint assessed at week 48. Rapid improvements were observed in pre-bronchodilator FEV1 and sustained improvements were seen in all outcome measures for patients given dupilumab who previously received placebo in parent studies; further improvements in AER, asthma control, and health-related quality of life were observed in patients who continued receiving dupilumab. Blood eosinophils and serum total IgE decreased progressively. ADA status had no effect on safety or efficacy. In the subgroup of patients with a type 2 inflammatory phenotype followed-up for 148 weeks, AER decreased progressively, and initial lung function improvements were sustained over 148 weeks. Interpretation: Data show that safety and efficacy of dupilumab in adult and adolescent patients with moderate-to-severe asthma are sustained when treatment is extended up to 148 weeks. These findings therefore support the long-term use of dupilumab in this patient population. Funding: Sanofi and Regeneron Pharmaceuticals.